2011
DOI: 10.1039/c0jm04256k
|View full text |Cite
|
Sign up to set email alerts
|

The one-step preparation of nanowires using a facile ultrafiltration technique: the case for biomedical chitosan and/or iron oxide nanowires

Abstract: This work presents the employment of a frequently-used ultrafiltration technique to drastically reduce the time required for the synthesis of chitosan nanowires, iron oxide nanowires and their complex nanowires. Instead of synthesizing iron oxide nanowires using time-consuming template and hydrothermal methods, a centrifugation force provides a tangential flow to force both iron ions and/or the diluted chitosan solution to pass through a filter and co-precipitate into nanowires within 1 min. Two parameters, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
1
2
0
1
Order By: Relevance
“…The XPS of Fe from Fe 3 O 4 samples demonstrated the existence of Fe 2p 1/2 and Fe 2p 3/2 peaks at 724 eV and 711.5 eV, respectively, which were close to the standard data of Fe 3 O 4 (figure 3(a)) [22]. The absence of a satellite peak at 718 eV indicated that the nanoparticles were actually Fe 3 O 4 , and not γ -Fe 2 O 3 , a common phase of iron oxide that shares nearly identical XRD patterns with Fe 3 O 4 (figure 3(a), inlet) [23]. A small but present Cl peak was observed, which may be from the excess iron chloride, but did not adversely influence cell responses and, thus, will require further investigation.…”
Section: Nanoparticle Characterizationsupporting
confidence: 77%
“…The XPS of Fe from Fe 3 O 4 samples demonstrated the existence of Fe 2p 1/2 and Fe 2p 3/2 peaks at 724 eV and 711.5 eV, respectively, which were close to the standard data of Fe 3 O 4 (figure 3(a)) [22]. The absence of a satellite peak at 718 eV indicated that the nanoparticles were actually Fe 3 O 4 , and not γ -Fe 2 O 3 , a common phase of iron oxide that shares nearly identical XRD patterns with Fe 3 O 4 (figure 3(a), inlet) [23]. A small but present Cl peak was observed, which may be from the excess iron chloride, but did not adversely influence cell responses and, thus, will require further investigation.…”
Section: Nanoparticle Characterizationsupporting
confidence: 77%
“…Recent studies on the preparation of nanoscale iron oxide aided by cellulose have focused mainly on composite materials. In these publications, cellulose of different origins acts as a supporting matrix for the formation of iron oxide and as a filler for the homogeneous distribution of presynthesized crystalline nanospecies. Other biomaterials have been shown to assist in the nanofabrication of iron oxide, such as silk, chitosan, chitin, proteins, yeast cells, and butterfly wings . A few publications describing the fabrication of porous hematite morphologies aided by sacrificial cellulose templating deal only with macroscopic cellulose-based objects such as wood, filter paper, or fibers fabricated from regenerated cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Trong các nghiên cứu này, cellulose từ các nguồn khác nhau ngoài việc đóng vai trò như một giá thể cho sự hình thành oxit sắt còn được xem như như một chất độn cho sự phân bố đồng thể của các cấu trúc nano tinh thể trước khi tổng hợp. Các vật liệu sinh học khác cũng đã được sử dụng làm giá mang trong việc chế tạo nano oxit sắt, như tơ tằm 25 , chitosan [26][27][28] , chitin 29 , protein 30 , nấm men 31 và cánh bướm 32 . Một vài các nghiên cứu đã công bố quá trình chế tạo các hematite xốp trên các giá mang là cellulose [33][34][35]…”
Section: Mở đầUunclassified